Uganda’s National Budget 2010/2011: How Strategic are the Budget Priorities? - Tabaire, Bernard; Okao, Jackie (ACODE Policy Dialogue Series, 2010)
The debate came three weeks after Hon. Bbumba read her 2010/2011 budget speech before Parliament. The theme of the budget was “Strategic Priorities to Accelerate Growth, Employment and Socio-Economic Transformation for Prosperity”. Now, long gone are the days when reading the budget in Uganda was a highly anticipated public event. Because the country has had a long period of macroeconomic stability with single digit inflation rates and a free foreign exchange regime, the presentation of the budget is just yet another state ritual. Virtually no new taxes are introduced these days. So it was surprising that a budget-related subject yielded an unusually lively debate. The discussion revolved around: The necessity of the Pay As You Earn (PAYE) tax. Getting value for money. The place of agriculture in the national economy. Politics as a constraint to efficient planning.